Pengaruh Pengaruh Model Brain Based Learning Terhadap Kemampuan Berpikir Kreatif Matematis Siswa - Astiti Yugianti; Sigid Edy Purwanto; Mimin Ninawati (Jurnal Inovasi Pendidikan Dasar, 2018)
The purpose of the research was to find out the influence of using Brain Based Learning model to mathematical creative thinking skills of student. The research method was quasi experiment with Posttest-Only Control Design. Population of this research are 60 students consist of 30 from experiment class and 30 from control class. The technique sampling was saturation sampling. The data analysis using T test. Prior to hypothesis testing, there were two prerequisite tests that consist of the normality test and homogeneity test. The result of prerequisite tests showed that both classes had the normal distribution and the same variance. Based on the t-test, it can be seen that there was an influence of Brain Based Learning model mathematical creative thinking.